PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DI SEKOLAH DASAR - Arman Maulana; Muhammad Syahrul Rizal; Rusdial Marta; Adityawarman Hidayat; Dwi Viora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, and improvement of students' social skills through the application of the Talking Stick cooperative learning model. The method used is classroom action research (CAR) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 15 fourth-grade students of SD Negeri 003 Muara Uwai in the odd semester of the 2024/2025 academic year. Data were collected through observations of teacher activities, student activities, and social skills, then analyzed descriptively quantitatively and qualitatively. The results of the study showed a gradual increase in students' social skills. In the initial conditions, the average social skills were only 57.38 with a very poor category and 20% completeness. After the implementation of Talking Stick, the results of the first cycle meeting I increased to 65.07 with a poor category, and the first cycle meeting II to 73.87 with a sufficient category. In the second cycle meeting I the average value reached 79.80 with a sufficient category, while in the second cycle meeting II it increased to 85.87 with a good category. Thus, it can be concluded that the implementation of the Talking Stick learning model can significantly improve the social skills of fourth-grade students at SD Negeri 003 Muara Uwai, from very poor to good.